Framework Administered Account for Selected Fund Activities : Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) Subaccount. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. The subaccount for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) Topical Trust Fund ('TTF') would be the second one under the SFA. This paper requests Executive Board approval to establish the AML/CFT TTF subaccount (the 'Subaccount') under the terms of the SFA Instrument.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Contributor; Financing; PP; Resources Of The Subaccount; Subaccount